Flâneuserie Reimagined: Ida and Purposeful Wandering. Issue 3 (23rd March 2023) - Foster, Monica
The nineteenth-century poet and philosopher Charles Baudelaire has become synonymous with the concept of the flâneur. The flâneur was typically a male who had the leisurely time to "stroll" and observe metropolitan life in all its delights and displeasures. This article examines Paweł Pawlikowski's 2013 film, Ida and reconceptualizes the concept of the flâneur and appropriates it to a female protagonist, a flâneuse, along with a new setting and time period: the countryside and 1960s Communist Poland. Engaging in flâneuserie in the city allows Ida to experience new things, but it is in the countryside where Ida will come to terms with an instructive truth.